The issue of the display of sensitive information in the state land cadastre and its publicity in the conditions military conflict - Dorosh, O.; Dorosh, Y.; Tarnopolskyi, A.; Dorosh, A. (Land Management, Cadastre and Land Monitoring, 2023)
The goal of the scientific work was to justify the need during the war in Ukraine to find a balance in the issue of limiting access to sensitive in terms of state and public security open data in the State Land Cadastre system to ensure the interests of national security and public interests. Information of interest to the aggressor should become inaccessible. This data selection should be made by the military and the Security Service and should not be publicly displayed. On the other hand – the rest of the information should be used by specialists in the field of geodesy and land management, construction and architecture, local self-government bodies with a certain number of persons with access to data. The author’s proposal is also that access to data, including open data, should be regulated and authorized. So it is proposed to classify them at the legislative level in terms of levels of sensitivity, methods of use, access regulations, and to define lists of sensitive information and ways of displaying it. The need to change the attitude towards information resources as free resources and transfer information to the status of an intangible asset with licensed access (analogue – software) was noted, because the introduction of information into economic circulation will cause the growth of the economy. It is proposed that upon the end of martial law, the restrictions that were in force under these conditions should be reviewed, amendments to the legislation should be introduced into the regulations of the State Land Cadastre, and the composition, content, and distribution capacity of the cartographic base of the Public Cadastre Map should be updated.